34 Can Exercise Induced Changes in Cardiac Synchrony Predict Response to CRT? – Primary Results from the Exert Trial. (6th June 2015) - Zalen, Jet van; Patel, Nik; Raju, Prashanth; Beale, Louisa; Brickley, Gary; Lloyd, Guy
Abstract : Introduction: Cardiac resynchronisation therapy (CRT) improves symptoms of heart failure (HF) in the majority of patients but echocardiographic measures of selection have produced disappointing results. These measurements are often carried out at rest. Exercise can alter the magnitude and extent of ventricular dyssynchrony and dynamic changes vary between patients. The aim of this study was to determine whether changing dyssynchrony by exertion would predict a positive response to CRT. Method: 38 patients with symptomatic heart failure were included in this study. All patients had a depressed LVEF (<35%) and were clinically selected for CRT therapy. Two comparator groups were formulated: Phasers – subjects whose total mechanical delay (normalised for RR interval) decreased with exercise, and dephasers – subjects whom normalised mechanical remained stable or increased. Mechanical delay was defined from spectral tissue Doppler imaging, time from R wave to onset of post isovolumic S' at the lateral right and left ventricular annular and interventricular septum. The primary end point was VO2peak at 3 months post implant. Results: The overall population showed significant improvements in NYHA class, quality of life, LVEF, resting S', end diastolic and systolic volumes, and dimensions following CRT at 3 months. No significant improvements were observed for exercise parameters including VO2peak. 14 phasers and 24 dephasers were identified and no differences were found for VO2peak or for any other parameters obtained at 3 months (table 1). Conclusion: All patients showed that CRT significantly improved echocardiographic and functional parameters, no improvements were observed for exercise parameters. Exercise dyssynchrony was unable to identify if patients responded positively to CRT therapy. Both phasers and dephasers responded in a similar way to CRT.